Non-isothermal decomposition kinetics of magnesite - Maitra,S. (2007)
Kinetics of thermal decomposition of Indian magnesite was studied by thermo-gravimetric analysis under non-isothermal condition. Coats and Redfern Integral approximation method was used to determine the kinetic parameters. Using the kinetic parameters different kinetic functions were analyzed with the experimental data to ascertain the decomposition mechanism of magnesium carbonate and it was observed that the decomposition reaction followed a contracting sphere kinetic mechanism.